2018
DOI: 10.1017/jfm.2018.560
|View full text |Cite
|
Sign up to set email alerts
|

Statistical state dynamics of vertically sheared horizontal flows in two-dimensional stratified turbulence

Abstract: Simulations of strongly stratified turbulence often exhibit coherent large-scale structures called vertically sheared horizontal flows (VSHFs). VSHFs emerge in both twodimensional (2D) and three-dimensional (3D) stratified turbulence with similar vertical structure. The mechanism responsible for VSHF formation is not fully understood. In this work, the formation and equilibration of VSHFs in a 2D Boussinesq model of stratified turbulence is studied using statistical state dynamics (SSD). In SSD, equations of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 80 publications
(112 reference statements)
3
22
2
Order By: Relevance
“…This behavior is in contrast to the usual observation in β -plane turbulence that jets transition to lower wavenumber as the excitation strength is increased (Farrell and Ioannou 2007). Our previous analysis of VSHF formation with matrix S3T is consistent with this interpretation, and also suggests that additional turbulent equilibria consisting of lower-wavenumber, more energetic VSHFs may be simultaneously stable with the equilibria shown in Figure 8 (Fitzgerald and Farrell 2016).…”
Section: Stability Boundaries a Iresupporting
confidence: 71%
See 4 more Smart Citations
“…This behavior is in contrast to the usual observation in β -plane turbulence that jets transition to lower wavenumber as the excitation strength is increased (Farrell and Ioannou 2007). Our previous analysis of VSHF formation with matrix S3T is consistent with this interpretation, and also suggests that additional turbulent equilibria consisting of lower-wavenumber, more energetic VSHFs may be simultaneously stable with the equilibria shown in Figure 8 (Fitzgerald and Farrell 2016).…”
Section: Stability Boundaries a Iresupporting
confidence: 71%
“…Although this result appears to contradict the results of the NL simulation shown in Section 2, which forms buoyancy layers, our previous work has shown that these buoyancy layers do not emerge in homogeneous turbulence but instead form nonlinearly once a finite-amplitude VSHF has emerged (Fitzgerald and Farrell 2016).…”
Section: A Isotropic Ring Excitation (Ire)contrasting
confidence: 62%
See 3 more Smart Citations